2022
DOI: 10.1183/13993003.01426-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intubation timing in patients with COVID-19 throughout the four waves of the pandemic: a matched analysis

Abstract: BackgroundThe primary aim of our study was to investigate the association between intubation timing and hospital mortality in critically ill patients with COVID-19-associated respiratory failure. We also analysed both the impact of such timing throughout the first four pandemic waves and the influence of prior non-invasive respiratory support on outcomes.MethodsThis is a secondary analysis of a multicentre, observational and prospective cohort study that included all consecutive patients undergoing invasive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Supporting this clinical practice, a recent meta-analysis suggests that timing of intubation may have no effect on mortality and morbidity of critically ill patients with COVID-19 [48]. Other studies suggest contradictory results [49, 50]. Moreover, we did not compare ventilatory strategies or complications which would have influenced weaning from invasive MV [51].…”
Section: Discussionmentioning
confidence: 93%
“…Supporting this clinical practice, a recent meta-analysis suggests that timing of intubation may have no effect on mortality and morbidity of critically ill patients with COVID-19 [48]. Other studies suggest contradictory results [49, 50]. Moreover, we did not compare ventilatory strategies or complications which would have influenced weaning from invasive MV [51].…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, 67 HFNO showed an efficacy in reducing mortality compared with Noninvasive mechanical ventilation (NIMV) if associated with early intubation in patients with acute respiratory failure from SARS-CoV-2, but the latest 2023 ESICM guidelines about ARDS could not elaborate definitive recommendations due to this persistent lack of evidence. 68 Therefore, new clinical studies are needed to investigate differences in terms of mortality and intubation rate between groups of patients treated with HFNO and NIV.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The definitions of early and late intubation varied from previously temporal criteria to the current clinical classification based on the patient's clinical features before intubation. (Table 1) 30,32,[34][35][36][37][38][39] Therefore, there seems to be no concise intubation timing. The ROX index (SpO 2 /FiO 2 /breathing frequency), PaO 2 / FiO 2 ratio, and other clinical features, such as respiratory rate and hemodynamics, were recommended as indications for intubation.…”
Section: Intubation Timingmentioning
confidence: 99%